2019
DOI: 10.1007/s11244-019-01206-w
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Heating Assisted-Catalytic Dehydrogenation of Tetralin as a Hydrogen Source for Downhole Catalytic Upgrading of Heavy Oil

Abstract: The Toe-to-Heel Air Injection (THAI) combined with a catalytic add-on (CAPRI, CATalytic upgrading PRocess In-situ) have been a subject of investigation since 2002. The major challenges have been catalyst deactivation due to coke deposition and low temperatures (~ 300 °C) of the mobilised hot oil flowing over the catalyst packing around the horizontal well. Tetralin has been used to suppress coke formation and also improve upgraded oil quality due to its hydrogen-donor capability. Herein, inductive heating (IH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The majority of the pelleted catalyst pore volume contribution is from mesopores with a pore diameter in the range of 6-12 nm, with a much smaller contribution from pores with a diameter less than 5 nm and greater than 12 nm. The catalyst acid sites happened at 280 °C (0.62 mmol adsorbed (CH3)3CNH2 g −1 ) and 480 °C (0.12 mmol adsorbed (CH3)3CNH2 g −1 ), while X-ray diffraction pattern revealed alumina peaks at 46° and 67°, nickel oxide 37.3° and molybdenum oxide 33.6°; these have been reported elsewhere [17].…”
Section: Catalyst Characterizationsupporting
confidence: 66%
See 4 more Smart Citations
“…The majority of the pelleted catalyst pore volume contribution is from mesopores with a pore diameter in the range of 6-12 nm, with a much smaller contribution from pores with a diameter less than 5 nm and greater than 12 nm. The catalyst acid sites happened at 280 °C (0.62 mmol adsorbed (CH3)3CNH2 g −1 ) and 480 °C (0.12 mmol adsorbed (CH3)3CNH2 g −1 ), while X-ray diffraction pattern revealed alumina peaks at 46° and 67°, nickel oxide 37.3° and molybdenum oxide 33.6°; these have been reported elsewhere [17].…”
Section: Catalyst Characterizationsupporting
confidence: 66%
“…In this study, under nitrogen gas atmosphere with induction heating (i.e., interior-to-exterior), the API gravity of the upgraded oil samples increased in ranges from 4.5 to 9.7 • , and viscosity about 45 mPas, representing about 2.4 • API gravity points above that achieved by conventional heating method. The temperature of the catalytic bed during tetralin dehydrogenation reaction for both conventional and induction heated catalytic bed was reported by Hart et al [17]. In this earlier study, it was observed that the surface of the catalyst during reaction was hotter with induction heating with steel balls than with conventional heating with a furnace at 300 • C experimental temperature [17].…”
Section: Api Gravity and Viscositymentioning
confidence: 72%
See 3 more Smart Citations